EFFECT OF SODIUM HYPOCHLORITE, PHOTOPERIOD AND TEMPERATURE ON IN VITRO ESTABLISHMENT OF “JABUTICABA” TREE - PICOLOTTO, Luciano; SCHUCH, Márcia Wulff; SOUZA, Joseane Almeida de; SILVA, Luciane Couto; FERRI, Juçara; FACHINELLO, José Carlos (Scientia Agraria, 2007)
The aim of this work was to test the influence of different concentrations of sodium hypochlorite, photoperiod and temperature on the disinfestations and in vitro germination of "jabuticaba" seeds. The used culture medium was MS. The "jabuticaba" seeds kept under two conditions for 8 days at 5 ºC and room temperature were disinfested in 2,5% and 5,0% sodium hypochlorite solution and then inoculated in test tubs containing 10 mL of medium. After inoculation 50% of the seeds were placed in the darkness under 25 ± 2 ºC and 50% were transferred to the growth room at the same temperature, with 16-hours photoperiod and radiation of 27 µmol m-2 s-1. The assessments of bacteria and fungi contamination percentage and oxidation percentage were done during the 7th, 14 th, 21 th, 28 th and 35th day of the cultivation. Also on the 42th cultivation day it was evaluated the germination percentage. The seeds submitted to 5 ºC had the highest germination percentage. The 5,0% sodium hypochlorite solution showed efficient in the disinfestations decreasing fungi contamination. The lowest bacteria contamination occurred in the seeds kept at room temperature in the light presence. It was concluded that the "jabuticaba" seeds germination was influenced by the temperature, and the photoperiod did not appear to have an effect. The fungi contamination is inversely proportional to the used disinfector concentration showing no influence in the bacterial contamination.